Beneficial effects of natural flavonoids on neuroinflammation - Chen, Yu; Peng, Fu; Xing, Ziwei; Chen, Junren; Peng, Cheng; Li, Dan (Frontiers in Immunology, 2022)
Neuroinflammation is a fundamental immune response to protect the brain, and also triggers neuronal damage under excessive or chronic situation. Moreover, neuroinflammation characterized by the production of inflammatory mediators is one of the most common pathological outcomes in various brain disorders. Flavonoids, as a species of important natural compounds, exhibit beneficial effects in neuroinflammation-related brain disorders. Flavonoids could inhibit the up-regulation of pro-inflammatory mediators, increase the secretion of anti-inflammatory factors, regulate microglia polarization and inhibit astrocyte proliferation. And the mechanisms mainly include suppressing the activation of NLRP3 inflammasome as well as NF-κB, MAPK, and JAK/STAT pathways, promoting Nrf2, AMPK, BDNF/CREB, and Wnt/β-Catenin pathways and regulating PI3k/Akt pathway and SIRT1-mediated HMGB1 deacetylation to exert anti-neuroinflammatory effects. This collective information provides comprehensive knowledge on therapeutic benefits and mechanisms of natural flavonoids in brain disorders by targeting neuroinflammation, and hope to provide reference for formulating nutritional guidelines and therapeutic strategies to neuroinflammation-related brain diseases.